Peran Audit dalam Mencegah Kecurangan: Tinjauan dari Perspektif Etika Bisnis - Diajeng Cantika Triciyana; Della Ayunda Prameswari; Yuni Sukandani (STIKes Ibnu Sina Ajibarang, 2025)
Fraudd in the bussines world has become a major challenge that can harm various parties, including companies to other stakeholders, often triggered by ethical lapses in the bussines environment.This study discusses the role of internal audit in preventing fraud from a bussines ethics perspective and identifies factors that affect the efficieness of internal audit. The data analysis technique used is descriptive analysis. The research method used is qualitative through a literature review approach or library research, which is carried out by analyzing and reviewing literature sources and scientific publications related to the research topic. The results pf analysis show that internal audit has a crucial role as the frontile in mitigating the risk of fraud through supervisory functions, evaluating the internal audit is influenced by auditor competence and independence, top management support, eduquate audit coverage, and the application of targeted audit methodologies. Therefore, organizations need to optimize the internal audit function by improving auditor competence, implementing advanced audit technology, and ensuring full support form top management to create a transparent and accountable bussines environment.